27 High definition lipoproteomics reveal dysregulated redox proteins in coronary artery disease. (17th November 2015) - Bhandari, Sanjay S; Kanagala, Prathap; Jones, Donald JL; Ng, Leong L
Abstract : Background: Lipoproteins have an integral role in the pathogenesis of CAD. Quantitative proteomics is evolving to become an indispensable tool in the era of precision medicine. Using an unbiased lipoproteomic discovery workflow we sought to investigate the lipoproteomic differences between stable CAD patients and controls subjects and to reveal novel pathways/mechanisms that underpin this common disease. Methods: Male patients with stable CAD (n = 49, mean ± SD; age 64 yrs ± 8.69) and without CAD (n = 17; mean age 74 yrs ± 6.21) were recruited into this single centre prospective cohort study. Plasma was co-incubated with a lipophilic affinity resin. Isolated lipoproteins were reduced, alkylated, digested and analysed using label-free high definition ion mobility enabled mass spectrometry. Raw data was analysed using Progenesis QI software with a stringent false discovery rate of 1%. Results: 202 proteins showed significant differential expression between the CAD patients and the control subjects (P < 0.05). CAD patients had selective depletion of antioxidants; glutathione peroxidase 3 (GPX3) (p < 1e-28), clusterin (p < 1e-12) and serum paroxonase-1 (PON1) (p < 1e-7) compared with controls. Furthermore, there was selective up-regulation of proteins concerned with inflammation; serum amyloid A-1 (p < 1e-12), mannan binding lectin serine protease 1 (MASP1) (p < 1e-8) and galectin-3-binding protein (p = 0.001) in the CAD patients compared with the control subjects. Phospholipid transfer protein (PLTP) (p < 0.001) and apolipoprotein (a) (p = 0.002) were over expressed in the CAD patients. Conclusion: Patients with CAD have a distinct pathognomonic lipoproteomic cargo. The measurement of certain lipoprotein associated proteins may assist in the early identification of such patients before symptom onset.